Plantation Industry Firm Value: The Factors of Profitability, Leverage, and Company Size - Kurnianingtyas, Rinita Mutiarasani; Yuliati, Anik (PT Global Digital Sains Tekno, 2023)
Company value is a parameter for investors' assessment of a company's success, which is closely related to share prices. This research aims to test and prove the influence of Profitability, Leverage, and Company Size on Firm Value in plantation companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This research uses a quantitative approach. The population of this research is plantation companies listed on the Indonesia Stock Exchange for the 2015-2019 period, totaling 21 companies. The sample used in this research was 12 plantation companies with a period of 5 years, so the total data (n) was 60. This research data is secondary data from company financial reports from the company website and www.idx.co.id. The method used in this research is Purposive Sampling. The data collection method uses the documentation method. The data analysis used in this research is the multiple linear regression analysis tool and hypothesis testing, namely the F test, t-test, and coefficient of determination; classical assumption tests include the normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. Based on the analysis that has been carried out, it can be concluded that Profitability (ROE) contributes to company value. On the other hand, Leverage (DAR) and Company Size do not contribute to company value.